Persistent breeding-induced endometritis in mares - a multifaceted challenge: From clinical aspects to immunopathogenesis and pathobiology - Canisso, Igor F.; Segabinazzi, Lorenzo G.T.M. [UNESP]; Fedorka, Carleigh E. (MDPI, 2020)
Post-breeding endometritis (i.e., inflammation/infection of the endometrium), is a physiological reaction taking place in the endometrium of mares within 48 hours post-breeding, aimed to clear seminal plasma, excess sperm, microorganisms, and debris from the uterine lumen in preparation for the arrival of an embryo. Mares are classified as susceptible or resistant to persistent breeding-induced endometritis (PBIE) based on their ability to clear this inflammation/infection by 48 hours post-breeding. Mares susceptible to PBIE, or those with difficulty clearing infection/inflammation, have a deficient immune response and compromised physical mechanisms of defense against infection. Molecular pathways of the innate immune response known to be involved in PBIE are discussed herein. The role of the adaptive uterine immune response on PBIE remains to be elucidated in horses. Advances in the pathobiology of microbes involved in PBIE are also revised here. Traditional and non-traditional therapeutic modalities for endometritis are contrasted and described in the context of clinical and molecular aspects. In recent years, the lack of efficacy of traditional therapeutic modalities, alongside the ever-increasing incidence of antibiotic-resistant microorganisms, has enforced the development of non-traditional therapies. Novel biological products capable of modulating the endometrial inflammatory response are also discussed here as part of the non-traditional therapies for endometritis.
Keywords: Endometrium; Horses; Inflammation; Subfertility; Uterine infection